I posed a generalization of Theorem 3.2 In my paper

Conjecture: Let $P_1, P_2,....,P_{2n+1}$ and $O$ be $2n+2$ points in plane. Construct a chain $2n+1$ regular ${2n+1}$-gons $A_{1\;1}A_{1\;2}...A_{1\;2n+1}$; ....;$A_{2n+1\;1}A_{2n+1\;2}...A_{2n+1\;2n+1}$ with center $A_1, A_2...., A_{2n+1}$ such that $A_{1\;1}=O$, $A_{1\;2}=P_1$, $A_{2\;1}=A_{1\;3}$, $A_{2\;2}=P_{2}$, $A_{i+1\;1}=A_{i\;3}$, $A_{i+1\;2}=P_{i+1}$ for $i=\overline{1\;2n}$

enter image description here

Continuing construct a chain $2n+1$ regular ${2n+1}$-gons $B_{11}B_{12}...B_{1\;2n+1}$; ....;$B_{2n+1\;1}B_{2n+1\;2}...B_{2n+1\;2n+1}$ with centers $B_1, B_2...., B_{2n+1}$, such that $B_{1\;1}=A_{2n+1\;3}$, $B_{1\;2}=P_1$, $B_{2\;1}=B_{1\;3}$, $B_{2\;2}=P_{2}$, $B_{i+1\;1}=B_{i\;3}$, $B_{i+1\;2}=P_{i+1}$ for $i=\overline{1\;2n}$.

Then $B_{2n+1\;3}=O$ and segments $A_1B_1=A_2B_2=...=A_{2n+1}B_{2n+1}$ and $\angle (A_iB_i, A_{i+1}B_{i+1})=\frac{(2n-1)\pi}{2n+1}$

Corollary: $B_{2n+1\;3}$ is fixed point when $P_1$, $P_2$, ....,$P_n$ be moved.

Question 1: Is the conjecture correct?

Question 2: Let $P_1$, $P_2$, ....,$P_n$ are fixed point in the plane, find position of $O$ such that $A_{2n+1\;3}=O$

See also:

PS: In the conjecture, all regular polygon is same direction.

  • $\begingroup$ Nice question ! $\endgroup$
    – Alkan
    Commented Jul 27, 2020 at 10:43
  • $\begingroup$ Thanks you, I correction @FedorPetrov $\endgroup$ Commented Jul 27, 2020 at 14:01

1 Answer 1


You may easily calculate everything in complex numbers. Denote $m=2n+1$, $w=e^{2\pi i/n}$, $Q_i=A_{i,3}=A_{i+1,2}$ for $i=i,2,\ldots$. We may suppose that $P_{m+i}=P_i$ for $i=1,\ldots,m$ and we have one sequence of $2m$ polygons. Then we have to prove $Q_{2m}=O$ (let $O=0$ be the origin) and that $C_k:=A_{k+m}-A_k$ satisfy $C_{k+1}=-w C_k$. This follows from $Q_k-P_k=(P_k-Q_{k-1})w$, where $Q_0=0$. Dividing by $w^k$ this gives for the sequence $R_k:=(-1)^kQ_k/w^k$ the recurrence $R_k-R_{k-1}=(-1)^kP_k(1+w)/w^k=:x_k$. We have $x_{m+k}+x_k=0$, thus $R_{2m}=x_1+\ldots+x_{2m}=0$. Also $A_k=(Q_k-P_kw)/(1-w)$, thus $$C_k=A_{k+m}-A_k=\frac{1}{1-w}(Q_{k+m}-Q_k)=(-1)^{k}\frac{w^k}{1-w}(R_k+R_{m+k})= (-1)^{k}\frac{w^k}{1-w}(x_1+\ldots+x_k+x_1+\ldots+x_{m+k})= (-1)^{k}\frac{w^k}{1-w}(x_1+\ldots+x_m),$$ the result follows.

As for question 2, it asks when $x_1+\ldots+x_m=0$. Since $O$ is variable, we replace $P_i$ to $P_i-O$ and get the equation $$ \sum_{k=1}^m (-1)^k (P_k-O)/w^k=0 \Leftrightarrow O=\frac{1+w}2\sum_{k=1}^m (-1)^{k-1}P_k w^{-k}. $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.